2014
DOI: 10.4049/jimmunol.1300837
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Requirements for Activation of NKT and NK Cells during Viral Infection

Abstract: Natural killer (NK) cells are key regulators of innate defense against mouse cytomegalovirus (MCMV). Like NK cells, NKT cells also produce high levels of IFNγ rapidly after MCMV infection. However, whether similar mechanisms govern activation of these two cell-types, and the significance of NKT cells for host resistance, remain unknown. Here we show that although both NKT and NK cells are activated via cytokines, their particular cytokine requirements differ significantly, in vitro and in vivo. IL-12 is requir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
56
1
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(61 citation statements)
references
References 56 publications
3
56
1
1
Order By: Relevance
“…Cytokines from innate immune cells can act together with TCR signals to induce cytokine production from iNKT cells. Furthermore, apart from cognate, TCRmediated activation; there is evidence that iNKT cells from mice and humans also can be activated by cytokines from innate immune cells elicited by TLR signals and other stimuli, in a TCR-independent fashion (Holzapfel, Tyznik, Kronenberg, & Hogquist, 2014;Leite-De-Moraes et al, 1999;Nagarajan & Kronenberg, 2007;Smithgall et al, 2008;Tyznik et al, 2008;Tyznik, Verma, Wang, Kronenberg, & Benedict, 2014). In this section, we provide further details on the various modes of iNKT cell activation and the role of these cells in different infections.…”
Section: Diverse Modes Of Inkt Cell Activationmentioning
confidence: 99%
See 2 more Smart Citations
“…Cytokines from innate immune cells can act together with TCR signals to induce cytokine production from iNKT cells. Furthermore, apart from cognate, TCRmediated activation; there is evidence that iNKT cells from mice and humans also can be activated by cytokines from innate immune cells elicited by TLR signals and other stimuli, in a TCR-independent fashion (Holzapfel, Tyznik, Kronenberg, & Hogquist, 2014;Leite-De-Moraes et al, 1999;Nagarajan & Kronenberg, 2007;Smithgall et al, 2008;Tyznik et al, 2008;Tyznik, Verma, Wang, Kronenberg, & Benedict, 2014). In this section, we provide further details on the various modes of iNKT cell activation and the role of these cells in different infections.…”
Section: Diverse Modes Of Inkt Cell Activationmentioning
confidence: 99%
“…4C). Other studies have provided evidence for a purely cytokine-mediated activation of iNKT cells to produce IFNγ, with no requirement for a TCR-CD1d interaction (Leite- De-Moraes et al, 1999;Nagarajan & Kronenberg, 2007;Smithgall et al, 2008;Tyznik et al, 2008Tyznik et al, , 2014Wesley, Tessmer, Chaukos, & Brossay, 2008). Furthermore, using Nur77 GFP transgenic mice, which have a reporter gene construct that indicates TCR-mediated activation, it was shown that expression of the TCR reporter occurred in vivo with microbes having foreign antigens, including S. paucimobilis and S. pneumoniae, but not with microbes lacking a foreign antigen, such as S. typhimurium and mouse cytomegalovirus (MCMV) (Holzapfel et al, 2014).…”
Section: Cytokine-mediated Activation Of Inkt Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…Latent HCMV is present in the majority of people worldwide, but the primary infection is usually asymptomatic. The primary infection is well contained by the immune cells, such as natural killer (NK) cells and T cells, which also prevent viral reactivation from latency (1,2).Their activation depends on cross talk with dendritic cells (DC) (3,4), and this interaction plays an important role in CMV control (5)(6)(7). The direct effect of DC on viral replication remains, however, unclear.…”
mentioning
confidence: 99%
“…Although T cells are critical in controlling CMV latency and preventing reactivation (Hanley and Bollard 2014), a role for host NK cells has been established in the acute stages of this infection (López-Botet et al 2014;Tyznik et al 2014). This DNA virus has been present in the human population for thousands of years and as such has evolved clever mechanisms of immune evasion, while simultaneously leaving an imprint on the human genome with respect to NK cell recognition of virus (Gumá et al 2004;Vidal and Lanier 2006;Brizić et al 2014).…”
Section: Nk Cell Memory Following Mouse Cytomegalovirus Infectionmentioning
confidence: 99%